The Relationship between Organization Structures and Performance in the Nigerian Public Sector - Olanrewaju Yemisi Esther; Sanni Mubaraq; Lateef Saheed Ademola; Aliu Ismaila Daudu (STIM LASHARAN JAYA MAKASSAR, 2020)
The main purpose of instituting good organizational structure as a parameter for public sector governance control practices is to resolve issues affecting the prudent management of resources to ensure effective public service delivery. However, quality of public service delivery only increased by an aggregate average of 2.4 percent from 2008 to 2017 as a result of poor organization structure. This implies that existence organization structure seems not useful due to the level of decay in public service delivery. Consequently, the present study assesses the relationship between organizational structure tools such communication with stakeholder, accountability and internal control on performance of Nigerian public sector. The study employed the two popular survey research instruments (questionnaire and interview) to collect data concurrently, analyzes separately and merged the results during interpretations. The target population for quantitative analysis is made up of Six (6) from each of the 175 MDAs in Nigeria as at December, 2018 while the study proposed Ten (10) participants for interviews. The quantitative data were analysed using descriptive and inferential statistic. The Partial Least Square Structural Equation Modelling (PLS-SEM) was used to test the hypotheses. The findings of the study from quantitative and qualitative analysis reveal that communication with stakeholder; accountability and internal control are positively and significantly associated with public sector performance. The study concludes that the three constructs proxied for organization structure have positive influence on the public sector performance. Therefore, the study recommends that all the heads of MDAs should lay more emphasis on transparency and accountability in order to be accessible independently by the public, the internal control system of MDAs should be regularly review and updated to achieve the stated public service objective and all MDAs staff should be training regarding the line of communication in public services in order to enhance public sector performance.